2021
DOI: 10.1002/cbin.11536
|View full text |Cite
|
Sign up to set email alerts
|

Metformin attenuates lipopolysaccharide‐induced epithelial cell senescence by activating autophagy

Abstract: Acute lung injury (ALI) is a life‐threatening medical condition with higher mortality and morbidity in elderly patients. Recently, metformin, a drug commonly used to lower blood glucose in type 2 diabetes patients, has been shown to be an effective anti‐inflammatory agent in ALI. However, the mechanism of this regulation still remains poorly understood. In our study, we found that epithelial cell senescence was elevated after lipopolysaccharide (LPS) exposure in vivo and in vitro, accompanied by decreased expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…Studies have shown that LPS can activate autophagosome formation in mice. These studies suggest that autophagy may be an adaptive response to LPS‐induced ALI, 33 which aligns with the results of our study. LPS can enhance autophagy and increase the expression of the autophagy‐related proteins, LC3II/I and Beclin1.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Studies have shown that LPS can activate autophagosome formation in mice. These studies suggest that autophagy may be an adaptive response to LPS‐induced ALI, 33 which aligns with the results of our study. LPS can enhance autophagy and increase the expression of the autophagy‐related proteins, LC3II/I and Beclin1.…”
Section: Discussionsupporting
confidence: 92%
“…32 Studies have shown that LPS can activate autophagosome formation in mice. These studies suggest that autophagy may be an adaptive response to LPS-induced ALI, 33 Autophagy is closely related to inflammation. The process of autophagy involves many relevant proteins that can swallow and kill pathogens to protect cells from pathogens and inhibit the secretion of inflammasomes and inflammatory factors.…”
Section: Discussionmentioning
confidence: 92%
“…Rapamycin protects alveolar epithelial cells from apoptosis and attenuates silica-induced pulmonary fibrosis through the enhancement of autophagy in the mouse model ( Zhao et al, 2019 ). Emerging evidence indicated that autophagy plays an import role in the beneficial effects of metformin ( Bharath et al, 2020 ; Ren et al, 2020 ).Metformin attenuates lipopolysaccharide-induced epithelial cell senescence by activating autophagy ( Wang et al, 2021 ). Bharath et al (2020) showed that metformin enhances autophagy and normalizes mitochondrial function to alleviate aging-associated inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies have focused on the contribution of senescent AT2 cells to the pathogenesis of lung diseases. A large number of senescent AT2 cells were found in COVID-19-induced acute lung injury (ALI), [104] ventilation, [105] influenza, [106] LPS, [107] and chronic lung diseases, such as lung fibrosis and COPD. [108 , 109] Senescent AT2 cells exhibited lower regenerative capacity, as demonstrated by their impaired regeneration-related signaling pathways, [108] decreased AT2 and AT1 cell markers, [110] minimal stemness markers, [111] and lower proliferation markers.…”
Section: Pulmonary Endogenous Stem Cellsmentioning
confidence: 99%